Optimizing Maritime Supply Chain Resilience with Port Integration and Inland Distribution at Base Pier - Moch Haris; Cahya Kusuma (AGUSPATI Research Institute, 2023)
The adverse impact of the Covid 19 pandemic on the maritime supply chain has been felt. Ensuring the stability and efficiency of maritime supply chains in the post-epidemic era is critical for economic recovery and social development, as it is the most important player in international trade. Fortunately, in order to enhance the sustainability of the maritime supply chain as a core industry, ports can strengthen cooperation by integrating with land transport companies. Pricing strategies for the decentralized, centralized and hybrid models are discussed and the effects of state regulation are analyzed. Based on the research results, it was found that if both shipping supply chains were centralized and provided exactly the same services, port congestion due to a crisis such as a pandemic would not significantly erode profits. Second, if the government steps in, maintaining some sort of decentralized supply chain for delivery is a much better option, and prices will go up for it. However, in order to increase the sustainability of the shipping supply chain, the decentralized structure needs to be urgently transferred to a centralized structure, and welfare may decrease when loss of time is high.